KONDISI EKSISTING RUANG TERBUKA HIJAU DI KAMPUS BINA WIDYA UNIVERSITAS RIAU PEKANBARU - Darmawati Darmawati; Aras Mulyadi; Suwondo Suwondo; Zulfan Saam (Program Pascasarjana Universitas Riau, 2022)
The campus is a part of the urban area. It needs spatial planning based on the applicable regulations. The arrangement and development of campus infrastructure must pay attention to the Green Open Space (GOS) availability according to the standards. This study aimed to determine the existing condition of the building area, GOS based on the area, GOS based on the needs of the number of academics, and absorption of CO2 emissions by vegetation at the Bina Widya Campus. The research method used quantitative and qualitative descriptive. The results showed that the existing condition of the building area was about 880.443 m2 or 25.48%, it has required the standard (max 60%). GOS based on an area was about 60.27%, it also has passed the regulations (min 30%), and non-GOS was approximately 14.25%, which exceeded the standard requirements (max 10%). The GOS based on the needs of the academic community was about 52.18 m2/person and has qualified the standards (min 20 m2/person). The Bina Widya Campus was covered with vegetation that has the capability to absorb CO2emissions of around 62.951,34 tons per year or it equaled the trees that covered a 114,17-acre area.